New operation analysis method for vacuum tube driving a tuned cavity - Jian Wu; Chunlin Zhang; Bin Wu; Hanyang Liu; Xiang Li; Yang Liu; Wei Long; Xiao Li (Physical Review Accelerators and Beams)
The rf system of China Spallation Neutron Source (CSNS) Rapid Cycling Synchrotron (RCS) utilizes vacuum tubes to drive the ferrite-loaded cavities. Ensuring stable tube operation in the rf system is crucial for the acceleration of high-intensity beams, as any instability may impede further increases in beam power. Therefore, the operation of the vacuum tube under heavy beam loading has attracted significant attention, particularly in the case of CSNS-II RCS, where the circulating beam current is expected to reach up to 15.25 A, imposing a substantial burden on the vacuum tube for beam loading compensation. Thus, a comprehensive analysis of tube operation is imperative. However, current methods for the tube operation analysis are developed based on wideband rf cavities, which are inadequate when the load of the tube is a narrowband ferrite-loaded cavity equipped with a tuning system. The presence of a tuning system renders the modeling method for wideband rf cavities inapplicable for ferrite-loaded cavities. Therefore, the development of a new method is necessary. This paper introduces a novel method for analyzing operation of vacuum tube driving a tuned cavity. The effectiveness of the method is validated by comparing the analysis results with measurements under beam loading conditions. Furthermore, an estimation of tube operation under 500 kW beam loading for CSNS-II is provided.